Theoretical Modeling of Triple‐Barrier Resonant‐Tunneling Diodes Based on AlGaN/GaN Heterostructures. Issue 23 (21st October 2019) - Rong, Taotao; Yang, Lin-An; Zhao, Ziyue; Zhang, Kai; Hao, Yue
Abstract : Herein, the performance of asymmetric triple‐barrier resonant‐tunneling diodes (TBRTDs) based on AlGaN/GaN heterostructures is investigated using numerical simulation. TBRTD can yield the current–voltage characteristics exhibiting two negative differential resistance (NDR) regions. Investigations show that the peak‐to‐valley current ratio (PVCR) can approach the value as high as 12.3 and the peak current density remains at a high value of 2 × 10 5 A cm −2 for the first NDR region, whereas the PVCR has a value of 2 and the peak current density can reach as high as the value of 9 × 10 5 A cm −2 for the second NDR region. Analysis shows that the introduction of the second quantum well (QW2) beside the main quantum well (QW1) can suppress the leakage current and alters the electron tunneling, which significantly improve PVCR and the reproducibility of NDR characteristic. An appropriate adjustment of QW2 and the Al component in the barrier can effectively modulate the number of NDR regions and their performances, which gives us great flexibility in device design. Abstract : The performance of asymmetric triple‐barrier resonant tunneling diodes (TBRTDs) based on AlGaN/GaN is investigated using numerical simulation. Firstly, TBRTDs can yield the current‐voltage characteristics exhibiting two negative differential resistance regions. Secondly, TBRTD shows a high peak‐to‐valley current ratio and reproducibility. Finally, an appropriate adjustment of the well and Al component can modulate the number of negative differential resistance (NDRs).